Hexacatenar liquid-crystalline complexes of palladium(II) and platinum(II) based on trialkoxystilbazole esters - Plasseraud, Laurent; Gonzalez Cuervo, Laura; Guillon, Daniel; Süss-Fink, Georg; Deschenaux, Robert; Bruce, Duncan W.; Donnio, Bertrand (My University, 2002)
The synthesis and characterisation of 4-(3,4,5-trialkoxybenzoyloxy)pyridines (1a–e), and of their corresponding palladium(II), (2a–e), and platinum(II), (3a–e), complexes are described. The pyridine-based ligands are not mesomorphic, but upon complexation to PdCl2 or PtCl2, new hexacatenar mesogens are formed which show exclusively the hexagonal columnar mesophase. The mesomorphic behaviour of the complexes was characterised by polarised optical microscopy, differential scanning calorimetry and X-ray diffraction. The metal seems to influence the crystal phase and mesophase stability as well as the mesomorphic temperature range.